Curing behavior of sodium carboxymethyl cellulose/epoxy/MWCNT nanocomposites. Issue 20 (25th April 2022) - Zhang, Jin; Tan, Lu; Dong, Hongxing; Qu, Wenshan; Zhao, Jianguo
Abstract : Kinetics calculated values and dynamic thermomechanical properties of CMC/CNTs/E44 systems. Abstract : The surfactant-assisted preparation of carbon nanotube (CNT)/polymer composites has attracted the attention of scientists around the world. Here, CNT/epoxy nanocomposites were prepared using sodium carboxymethyl cellulose (CMC). The effect of CMC on the curing behaviors of epoxy resin (E44) and CNTs/E44 was studied using differential scanning calorimetry (DSC). The curing kinetics of the CMC/CNTs/E44 systems were examined using methods where the activation energy ( E ) is a constant and where E is a variable, respectively. The change of E with the conversion ( α ) was calculated using the Starink isoconversional method. For the E44 system, a significant variation of E was observed when the conversion increased from 0.05 to 0.95. The E variable method was introduced to this system to describe this phenomenon. In contrast to the method where E is a constant, the E variable method has better agreement with the experimental data. With these two methods, the curing kinetics of the CMC/CNTs/epoxy system can be understood comprehensively and accurately. Ultimately, the dynamic mechanical properties of neat E44, CMC/E44 and CMC/CNTs/E44 were investigated and compared, which showed that CMC/E44 had a higher storage modulus ( E m ) than the neat E44 and CMC/CNTs/E44 systems, and the CMC/CNTs/E44 system had a higher glass transition temperature ( T g ) and damping factor (tan  δ ) than the neat E44 and CMC/E44 systems.